1977
DOI: 10.1104/pp.60.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of Linolenic Acid Synthesis in Winter Wheat Roots and Frost Hardening by BASF 13-338, a Derivative of Pyridazinone

Abstract: Treatment of 12-day-old winter wheat (Triticum aestivum) plants with BASF 13-338 {4-chloro-5(dimethylamino)-2-phenyl-3(2H)-pyridazinone} 36 hous before frost hardening simultaneousy and completely inhibit accumulation of linolenic acid in the roots during the hardening period and the acquiition of frost resistance. Increased asaturation of fatty acids is therefore probably an important part of the mechanism of cold adaptation in winter wheat.BASF 13-338 also prevents the increase in per cent dry weight in root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 10 publications
4
16
0
1
Order By: Relevance
“…BASF 13 338 treatment did not affect the levels of palmitic, stearic, and oleic acids (Table II). This effect was first observed by St. John (21) and subsequently confirmed by others (3,22,23,26). BASF 13 338 reduced the level of linolenic acid in mono-and digalactosyl diglycerides (21), in the polar lipid fraction (3,22,23) and in the total lipid fraction (3,26).…”
Section: Resultssupporting
confidence: 48%
See 3 more Smart Citations
“…BASF 13 338 treatment did not affect the levels of palmitic, stearic, and oleic acids (Table II). This effect was first observed by St. John (21) and subsequently confirmed by others (3,22,23,26). BASF 13 338 reduced the level of linolenic acid in mono-and digalactosyl diglycerides (21), in the polar lipid fraction (3,22,23) and in the total lipid fraction (3,26).…”
Section: Resultssupporting
confidence: 48%
“…Recent studies demonstrated that the substituted pyridazinone BASF 13 338 simultaneously inhibits the accumulation of linolenic acid and the acquisition of winter hardiness (22,23,26 was proposed that an increase in linolenic acid would increase the fluidity of membranes at low temperatures. This should enable wheat to function normally at low temperatures and perform the necessary steps involved in the acquisition of freezing resistance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Willemot (31) has shown that inhibition of linolenic acid biosynthesis in winter wheat roots by BASF 13.338 is accompanied by inhibition offrost hardening. St.…”
mentioning
confidence: 99%